Predicting sensory events. The role of the cerebellum in motor learning. - Nixon, P; Passingham, R (2001)
There is growing evidence that the cerebellum is involved in the implicit learning of movement sequences. On the serial reaction time (RT) task patients with cerebellar lesions fail to demonstrate normal decreases in RT and we have shown a similar effect in monkeys with bilateral cerebellar lesions. However, it is not clear if this impairment is unique to sequence learning or whether the cerebellum is also involved in the learning of discrete responses to predictable visual targets. We investigated this possibility in another group of monkeys with bilateral lesions of the cerebellum centred on the lateral nuclei. Three animals were pre-operatively trained to make rapid manual responses to a single target appearing on a touch-sensitive VDU screen. In one condition, a target could appear at any of three possible locations (spatially unpredictable). In a second condition the target always appeared in the same place (spatially predictable). A third condition was similar to the second except that the onset of the target was temporally predictable whereas in the previous conditions this parameter was randomized. Following the lesions, the RT savings earned on the conditions in which the cues were predictable were abolished. This was despite a lack of significant increase in movement times. The results imply that the animals were either failing to predict the spatial location or time of presentation of the target, or that they were unable to use their prediction to improve their reaction times. The function of the cerebellum in motor sequence learning may therefore be part of a more general operation in learning to prepare responses to predictable sensory events.